Spatiotemporal differences of land use pattern between mountainous areas and basin areas at township scale: A case study of Yuxi City - Wu, Li; Zhou, Jing; Xie, Binggeng; Yang, Sizhong; Li, Jingzhong (Frontiers in Environmental Science, 2022)
Land use/land cover change is an important carrier for the study of human-land relationship. Yuxi City is a typical area of with alternating mountain and basin landforms, forming a special human-land system with “mountains” and “basins” as the core elements. Taking 75 towns in Yuxi City, Yunnan Province as a case study, this paper uses a comprehensive evaluation model of land use/land cover change and related analysis methods to analyze the changes of land use pattern in mountainous areas and basin areas respectively from 1995 to 2018, and to reveal their spatial differences and its influencing factors. The results show that: 1) The dynamic evolution of land use in the mountainous area and the basin area presented obvious stage characteristics. From 1995 to 2005, the average comprehensive dynamic degree of land use in the mountainous area was 1.7861, which was significantly higher than the 1.7033 in the basin area. The average comprehensive dynamic degree of land use in mountainous areas from 2005 to 2018 was 1.1284, which was significantly lower than 1.9427 in the basin area. 2) From 1995 to 2018, the land use degree and the comprehensive dynamic degree of land use continued to rise in the basin area, while the mountainous area showed a trend of rising first and then falling. The overall change trend of land use depletion in the mountainous area was consistent with that in the basin area, but the mountainous area was always higher than that in the basin area. 3) The land use change in mountainous areas and basin areas was mainly reflected in the difference of natural factors and socio-economic fators. The radiation and agglomeration functions of the basin area have always attracted people to migrate from the mountains to the basin, which was beneficial to the ecological restoration of the vegetation in the mountains. Since the mountainous area and the basin area are geographically adjacent, the coupling and coordination of the two is the premise and foundation for the sustainable development of the region. This causal relationship of land use changes provides a reliable basis for the regulation of mountain-basin human-land coupling relationship.